Genotypic and phenotypic prevalence of Nocardia species in Iran: First systematic review and meta-analysis of data accumulated over years 1992-2021. - Mohammad Hashemzadeh (Public Library of Science (PLoS), 2021)
Background Nocardia species belong to the aerobic actinomycetes group of bacteria which are gram-positive and partially acid-fast Bacilli. These bacteria may sometimes be associated with nosocomial infections. Nocardia diseases are not required to be reported to public health authorities in Iran. Hence, the present study was designed to determine the prevalence of human Nocardia spp. in Iran by using a systematic review and meta-analysis according to the preferred reporting items for systematic reviews and meta-Analyses statement. Methods The data of the prevalence of Nocardia species were collected from databases such as Embase, PubMed/MEDLINE via Ovid, Web of Science, Scopus and Google Scholar as well as national Iranian databases, including SID, Magiran. Analyses were conducted by STATA 14.0. Results The meta-analyses showed that the proportion of Nocardia spp. in Iranian studies varied from 1.71(1.17, 2.24) to 0.46(0.09, 0.83). N. asteroides (21% [95% CI 1.17, 2.24]), N. cyriacigeorgica (17% [95% CI 0.99, 1.77]), N. facanica (10% [95% CI 0.75, 1.00]) were considered to be common causative agents. Conclusions Our study presents that despite the fact that Nocardia spp. are normally are saprophytic organisms, are currently accounts as emerging pathogens due to an increase in immunocompromised patients among Iranian populations. Considering our results, the establishment of advanced diagnostic facilities for the rapid detection of Nocardia infections are required for optimal therapeutic strategies of Nocardia spp. in Iran. Our findings could help the programmatic management of the disease within the context of Nocardia control programs.